Immunotherapy for colorectal cancer: where are we heading?. (3rd June 2017) - Basile, Debora; Garattini, Silvio Ken; Bonotto, Marta; Ongaro, Elena; Casagrande, Mariaelena; Cattaneo, Monica; Fanotto, Valentina; De Carlo, Elisa; Loupakis, Fotios; Urbano, Federica; Negri, Francesca V.; Pella, Nicoletta; et al.
ABSTRACT: Introduction : In the last few years, significant advances in molecular biology have provided new therapeutic options for colorectal cancer (CRC). The development of new drugs that target the immune response to cancer cells seems very promising and has already been established for other tumor types. In particular, the use of immune checkpoint inhibitors seems to be an encouraging immunotherapeutic strategy. Areas covered : In this review, the authors provide an update of the current evidence related to this topic, though most immunotherapies are still in early-phase clinical trials for CRC. To understand the key role of immunotherapy in CRC, the authors discuss the delicate balance between immune-stimulating and immune-suppressive networks that occur in the tumor microenvironment. Expert opinion : Modulation of the immune system through checkpoint inhibition is an emerging approach in CRC therapy. Nevertheless, selection criteria that could enable the identification of patients who may benefit from these agents are necessary. Furthermore, potential prognostic and predictive immune biomarkers based on immune and molecular classifications have been proposed. As expected, additional studies are required to develop biomarkers, effective therapeutic strategies and novel combinations to overcome immune escape resistance and enhance effector response.